The Use of Guiding Questions Technique to Improve The Students’ Writing Recount Text - Lutfiah, Lutfiah; Hidayat, Akhmad Nuris (LPPM Institut Pendidikan Nusantara Global, 2024)
Writing is one of the important skills in teaching English. More people need to learn writing in English for Jobs or academic terms. The researcher conducts this research to find the answer of the problem how the use of guiding questions technique can increase students’ writing recount text in the 22A pharmacy class of dr. Soebandi University. The design of this research is classroom action research. This research is covered four stages; they are planning, implementing, observing, and reflecting. Based on the result of writing test in cycle one which showed that the percentage of the students who got score 75 and higher was 60%. And in cycle two, it improved to be 73%. In addition, the average result of the students’ active participation was 65% in cycle one. In cycle two, the average result of the students’ active participation indicated improvement that was 75%. It can be concluded that the action in cycle two was successful. Finally, it can be concluded that the use of guiding questions technique can increase the 22A pharmacy class of dr. Soebandi University and can increase the 22A pharmacy students’ active participation in teaching learning process at dr. Soebandi University.